Correlation of Vit B12 levels with metformin usage among type 2 diabetic patients in a tertiary care hospital - Nareddy, Vishnu A.; Boddikuri, Indeevar P.; Ubedullah, Shaik K.; Papareddy, Abhinaya; Miriyam, Manoj Kumar (International Journal of Advances in Medicine, 2018)
Background: T2DM is a metabolic disorder that is increasingly becoming a public health concern. The disease is associated with a variety of systemic macrovascular and microvascular complications. Diabetic peripheral neuropathy (DPN) is the most common complication, and it may eventually develop in up to 50% of patients. It is assumed that prolonged use of metformin causes vitamin B12 deficiency. The clinical presentation of vitamin B12 deficiency generally includes haematological and neurological manifestations. The aim of the study is to correlate vit b12 levels in relation to duration of usage of metformin for a period of more than 1 year. Methods: The study was conducted from November 2017 to June 2018 for a period of 7 months which included 50 subjects from both sex groups, aged 18 years and above, on metformin with subjective evidence of neuropathy and compared with vit b12 levels. Results: The study results indicate that there is no significant drop in vit b12 levels in metformin users in significant proportions to cause vitb12 deficient-neuropathy. The p value being 0.658 comparing vit b12 with metformin usage years (<2 yrs, 2-5yrs, 5-8yrs, ≥8yrs). Conclusions: This cross-sectional study indicates that diabetic patients who were on metformin were not having any vit b12 deficiency, though all patients had subjective neuropathy. This suggests that neuropathy is not related to metformin induced Vit B12 deficiency. Therefore, prescribing of vit b12 supplementation in any long term metformin treated patients is no longer necessary and reduces patients financial burden.